Polyamine Resistance Is Increased by Mutations in a Nitrate Transporter Gene NRT1.3 (AtNPF6.4) in Arabidopsis thaliana - Tong, Wurina; Imai, Akihiro; Tabata, Ryo; Shigenobu, Shuji; Yamaguchi, Katsushi; Yamada, Masashi; Hasebe, Mitsuyasu; Sawa, Shinichiro; Motose, Hiroyasu; Takahashi, Taku (Frontiers in Plant Science, 2016)
Polyamines are small basic compounds present in all living organisms and act in a variety of biological processes. However, the mechanism of polyamine sensing, signaling and response in relation to other metabolic pathways remains to be fully addressed in plant cells. As one approach, we isolated Arabidopsis mutants that show increased resistance to spermine in terms of chlorosis. We show here that two of the mutants have a point mutation in a nitrate transporter gene of the NRT1/PTR family (NPF), NRT1.3 (AtNPF6.4). These mutants also exhibit increased resistance to putrescine and spermidine while loss-of-function mutants of the two closest homologs of NRT1.3, root-specific NRT1.1 (AtNPF6.3) and petiole-specific NRT1.4 (AtNPF6.2), were shown to have a normal sensitivity to polyamines. When the GUS reporter gene was expressed under the control of the NRT1.3 promoter, GUS staining was observed in leaf mesophyll cells and stem cortex cells but not in the epidermis, suggesting that NRT1.3 specifically functions in parenchymal tissues. We further found that the aerial part of the mutant seedling has normal levels of polyamines but shows reduced uptake of norspermidine compared with the wild type. These results suggest that polyamine transport or metabolism is associated with nitrate transport in the parenchymal tissue of the shoot.